2018
DOI: 10.1136/annrheumdis-2018-213223
|View full text |Cite
|
Sign up to set email alerts
|

Cleaved N-terminal histone tails distinguish between NADPH oxidase (NOX)-dependent and NOX-independent pathways of neutrophil extracellular trap formation

Abstract: These results indicate heterogeneity in NET-forming pathways and highlight the need for disease-specific strategies to prevent NET-mediated pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 51 publications
5
76
2
Order By: Relevance
“…The characteristics of these “pure” RNP ICx, which are distinct from the heterogenous autoantibodies and ICx derived from SLE patient serum investigated in the present study, likely explain the discrepancy with regard to whether or not NADPH oxidase is involved. Indeed, our finding of NADPH oxidase–independent formation of NETs in SLE was recently confirmed by others in studies that utilized a novel method for discriminating between NADPH oxidase–dependent and –independent NET formation .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The characteristics of these “pure” RNP ICx, which are distinct from the heterogenous autoantibodies and ICx derived from SLE patient serum investigated in the present study, likely explain the discrepancy with regard to whether or not NADPH oxidase is involved. Indeed, our finding of NADPH oxidase–independent formation of NETs in SLE was recently confirmed by others in studies that utilized a novel method for discriminating between NADPH oxidase–dependent and –independent NET formation .…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, non‐lytic NET formation is typically induced within minutes, and can be triggered by lipopolysaccharide (LPS) , specific bacterial products , Toll‐like receptor 4 (TLR‐4)–activated platelets , or complement proteins together with TLR‐2 ligands and SLE‐specific ICx. Non‐lytic NET formation can be independent of NADPH oxidase , but some studies have shown that NADPH oxidase can be involved . Importantly, the plasma membrane is not disrupted and NETs are released via vesicular transport while remaining viable, and typically contain oxidized mtDNA .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models of SLE, although with several limitations, tend to exclude a pathogenic role for NETosis in SLE 42,43 , apparently in accordance with the finding that NETosis-defective individuals (with impaired NADPH activity) are more prone to lupus-like disease than HD [39][40][41][42][43] . On the other hand, NET-like structures form in both a NADPH-dependent, or independent manner, and NET-like cell death due to autoantibodies does not seem to rely on NADPH activity 40,[44][45][46][47] . In our experiments, we observe that patient-derived anti-LL37 antibodies generated in vitro stimulate neutrophil extrusion of DNA filaments decorated by LL37.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil extracellular traps (NETs), an antimicrobial form of neutrophil death, were the first mechanism proposed to be associated with the production of citrullinated autoantigens in RA . This form of cell death is present in the RA joint, in vitro evidence suggests that neutrophils from patients with RA have increased susceptibility to form NETs, and in vivo evidence suggests that the formation of NETs is increased in RA . An association between NETs and citrullination was initially proposed by the finding that PAD4‐mediated citrullination of histones was necessary for NET formation in mice .…”
Section: Discovering the Origin Of The Intracellular Citrullinome In Ramentioning
confidence: 99%
“…76 This form of cell death is present in the RA joint, 76 in vitro evidence suggests that neutrophils from patients with RA have increased susceptibility to form NETs, 76 and in vivo evidence suggests that the formation of NETs is increased in RA. 80 An association between NETs and citrullination was initially proposed by the finding that PAD4-mediated citrullination of histones was necessary for NET formation in mice. 81 Later, this finding was erroneously taken as direct evidence that citrullination, particularly of histones, is a hallmark and exclusive marker of NETs.…”
Section: Neutrophil Extracellular Traps As Source Of the Ra Citrullmentioning
confidence: 99%